Bioethics in information technologies in telehealth: a systematic review - Santos, Waldeyde Oderilda Magalhães; Gonçalves, Isabela Cristina de Miranda; Duarte, Giovanna Gonçalves; Osis, Sibila Lilian; Farias, Altair Seabra; Santos, Daniel Magalhães; Sachett, Jacqueline de Almeida Gonçalves (Revista Bioética, 2025)
The growing use of technology inevitably leads to numerous debates on the ethical and legal issue of its use in healthcare. This research aims to investigate the bioethical aspects involved in information technologies use in telehealth actions via the synthesis of existing evidence so far, seeking a better understanding of this topic. A systematic review of the literature was conducted using on the Latin American and Caribbean Health Sciences Literature, MEDLINE, PubMed, Scientific Electronic Library Online, and Science Direct databases. This review identified several bioethical aspects involved in the use of information technologies, highlighting positive and negative points involving telehealth expansion, especially in developing countries, recognizing telehealth as a complementary method of access to health and not a substitute for traditional in-person consultations, which is even more important for the follow-up and monitoring of patients, mainly from remote areas or those with mobility difficulties.